99.9k views
4 votes
5. The steps for solving the equation 3x + 13 = x + 27 are shown below. What property justifies

the second step in the solution?
(1 point)
3x+13 = x+27
Step 1: -x - x
2x+13=
2x+13 = 27
Step 2: 1-13 -13
= 14
14
Step 3: 2
2
O additive identity
O additive inverse
O substitution
O subtraction property of equality

User Dies
by
5.8k points

2 Answers

2 votes

Answer:

In step 2 we applied the subtraction property of equality

Explanation:

The subtraction property of equality tells us that if we subtract from one side of an equation, we also must subtract from the other side of the equation to keep the equation the same.

In step 2 we did that:

2x + 13 - 13 = 2x + 27 - 13

(2x + 0 = 2x + 14)

2x = 2x + 14

User Jacobsieradzki
by
6.4k points
3 votes

Answer:

D. Subtraction property of equality.

Explanation:

We have been given an equation
3x+13=x+27. We are asked the property used in the second step of equation to solve it.

Step 1:


3x+13=x+27

Step 2:


3x-x+13=x-x+27

We can see that
x is subtracted from both sides of equation.

We know that subtracting same quantity from both sides of equation is known as subtraction property of equality.

Therefore, option D is the correct choice.

User Timothy Lombard
by
6.2k points